Factors influencing farmers' readiness to face Covid-19 post-movement control order challenges in Peninsular Malaysia - Mohd Pakri, Murni Azureen; Shah, Jasmin Arif; Mohamed Haris, Nur Bahiah; Mazlan, Norida (Universiti Malaysia Kelantan, 2022)
The COVID-19 pandemic is a global health catastrophe that has had severe effects on the worldwide economy, both directly and indirectly, because of the spread of the virus. The food and agriculture industries are also experiencing the effects. The COVID-19 epidemic disrupted the regular delivery system of agricultural extension services and the delivery of agricultural produce to markets. The study aimed to determine farmers' readiness to address post-MCO challenges in technology, implementation, decision-making, and leadership. Following the COVID-19 rules of reducing close contact to minimize virus transmission, a structured questionnaire was delivered to farmers online (Google form) and face-to-face with the support of extension agents. The results show that the relationship between independent and dependent variables was positive. Also, according to the findings, decision-making is the most crucial element influencing farmers' readiness to tackle post-movement control order issues. According to researchers, farmers' abilities should be developed to overcome challenges in pandemic conditions.